KNOWLEDGE AND AWARENESS AMONG DENTAL STUDENTS REGARDING SCREENING TECHNIQUES FOR DOWN SYNDROME DURING GESTATION - Manohar, Janhvi; Ganapathy, Dhanraj; Kumar Pandurangan, Kiran; Velayudhan, Ashok (International Journal of Psychosocial Rehabilitation, 2020)
Down syndrome is one of the most important causes of mental retardation in the world population. The purpose of prenatal screening is to identify those women at increased risk for an affected pregnancy and to maximize the options available to these women. Second trimester serum screening for chromosomal aneuploidies involves combining the maternal age-specific risk for an affected pregnancy with the risks associated with the concentrations of maternal serum alpha-fetoprotein (MSAFP), unconjugated estriol (uE3), and human chorionic gonadotropin (hCG) (triple testing). A fourth analyte, inhibin-A (INH-A), is increasingly being utilized (quadruple testing). These techniques, when employed with ultrasound soft marker scanning, give a true positive rate of 88% and significantly reduce the false positives. A questionnaire-based study was conducted among dental students of third and fourth year students and interns at a private dental college in Chennai, Tamilnadu, India, to assess their knowledge and awareness of prenatal screening techniques for Down syndrome. A multiple-choice questionnaire was presented to 106 subjects, and their responses were noted and tabulated, and statistical analysis was performed using SPSS by IBM by performing a chi-square test. Among 106 subjects, 40 (37.7%) were interns, 33 (31.13%) were third-year students, and the remaining 33 were fourth-year students. Interns and third-year students had more knowledge and awareness regarding the prenatal screening techniques employed to diagnose Down syndrome in fetuses with a significant p-value < 0.05.